The Mullerian Reconnaissance - Cutaneous Ciliated Cyst - Bajaj Anubha (Journal of Clinical and Diagnostic Pathology, 2019)
Cutaneous ciliated cyst is cogitated as a benign, exceptional lesion and can be additionally termed as cutaneous Mullerian cyst or a cystadenoma. Cutaneous ciliated cyst was initially described by Da Hess in 1890 and further elucidated in 1978 by Farmer and Helwig as a cyst predominantly occurring in young females within the second and third decades of life 12. Cutaneous ciliated cyst is a lesion of post- pubertal females, can appear in the reproductive phase and frequently enlarges during menstruation or pregnancy due to hormonal effects. Cutaneous ciliated cyst is commonly situated within deep-seated dermal or subcutaneous tissue of the upper extremities and perianal region. Cutaneous ciliated cyst delineates as Mullerian derivation in females and a distinct, foetal eccrine duct origin in males 12.
Keywords: Cutaneous ciliated cyst